ANEMIA IN CHILDREN WITH CHRONIC KIDNEY DISEASE - T.E. Pankratenko; T.Yu. Abaseeva; T.V. Margieva (Union of pediatricians of Russia, 2011)
Anemia is one of the most important issues in the chronic kidney disease treatment. As a rule, anemia is associated with a deficit of erythropoietin syntheses in the kidney. Recent studies have shown also the importance of iron deficiency - a relative or absolute. The authors demonstrate that the frequency and degree of anemia increases with progression of kidney disease i. e. losing of renal function. The iron metabolism investigation and the analysis of the therapy incomes lead the recommendations for optimization the treatment in consideration the potential causes of the therapy resistance.Key words: anemia, chronic kidney disease, classification, iron methabolizm, transferrin, ferritin, children.